Implementation of Religious Programs at Al-Azhar University in Medan - Ahmad Yamin Dalimunthe; Yusnaili Budianti; Sapri Sapri (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to: 1) analyze the planning of religious programs at Al-Azhar Medan College, Ar-Rahman Percut Middle School. 2) Analyze the implementation of religious programs at Al-Azhar Medan College, Ar-Rahman Percut Middle School. 3) Analyze the evaluation of religious programs at Al-Azhar Medan College, Ar-Rahman Percut Middle School. This study uses a qualitative research method with a narrative approach. Data collection was carried out through in-depth interviews, participatory observation, and document studies. Data analysis techniques include data reduction, data presentation and conclusion. The results of this study indicate that: (1) The planning of religious programs at Ar-Rahman Percut Middle School is based on the students' need for good religious education to get them used to worship and have good morals. The religious program is compiled and developed by the LPIA Al-Azhar Medan College. (2) The implementation of the religious program at Ar-Rahman Percut Middle School is structured and routine; some religious programs are implemented daily, weekly, monthly, and annually. (3) Evaluation of the religious program at Ar-Rahman Percut Middle School is carried out in five ways, namely daily evaluation, semester evaluation, annual program evaluation, student coaching and remedial.